Clinical and biochemical outcome in pediatric patients with iron deficiency anemia - Shah, Archana N.; Kothari, Jaini S.; Desai, Dhara P.; Savaliya, Tushar; Prajapati, Rajal B. (International Journal of Contemporary Pediatrics, 2020)
Background: Iron deficiency is a global public health problem with unique cultural, dietary and infectious hurdles that are difficult to overcome. Aims and objectives were to study clinical and biochemical profile of iron deficiency anemia, risk factors for iron deficiency anemia, presenting illnesses associated with iron deficiency anemia, association of other nutritional deficiency with iron deficiency anemia, treatment of iron deficiency anemia and recovery rate. Methods: This cross-sectional prospective study is conducted between June 2017 to May 2019in a tertiary care institute Gujarat state of India. All the children in the age group of 6 months to 5 years admitted in paediatric ward with anaemia were included in study. Data collection was done using a pretested questionnaire including socio-demographic factors. Data was analysed using statistical package for social sciences and excel and p<0.05 was considered as statistically significant. Results: The prevalence of anemia is 62.31% in patients admitted during study period. Mild to moderate anemia is observed in 75% patients. In present study, 62% patients are in age group of 6 months to 2 years and 38% patients are >2 years to 5 years. Patients with dimorphic anemia have initial mean serum B12 level 31.36 ng/ml, which improved after treatment to 312.98 ng/ml falling in the range of normalcy. Conclusion: Though anemia is common, most patients are stable and present with mild to moderate anemia. Only a fraction of patients presenting with congestive cardiac failure require packed red blood cells transfusion. Oral iron therapy for three months is the mainstay of treatment for iron deficiency anemia. Vitamin B12 therapy is also needed in patients with dimorphic anemia.